Accidental Hypothermia and Related Risk Factors among Trauma Patients Admitted to the Emergency Department - Roghayeh Hassandoost; Mohammadreza Dinmohammadi; Mahin Roohani (Zanjan University of Medical Sciences and Health Services, 2021)
Background: Early detection and management of hypothermia are determinants in the consequences of the injury. Various factors are involved in the progress of accidental hypothermia in these patients. Objectives: This study was done to determine the prevalence of accidental hypothermia and its related factors in trauma patients admitted to the emergency department (ED). Methods: In this prospective observational study, 123 trauma patients, who were transferred to the ED of Ayatollah Mosavi hospital, Zanjan, Iran by emergency medical technicians during November 2018, were selected. The patients' core body temperature (CBT) was measured through a calibrated tympanic thermometer on admission, 30 minutes after admission, and at the time of leaving the ED. Personal, clinical, environmental, and caring variables were evaluated as factors associated with hypothermia. Data were analyzed using descriptive statistics and multiple linear regression by SPSS16. The significance level was considered to be 5%. Results: The prevalence of accidental hypothermia in the ED was 43.1%. The patient's arrival CBT (β: 0.333, P-value <0.001), the length of stay in the ED (β: - 0.174, P-value =0.011), arrival ambient temperature (β: 0.165, P-value =0.039), and Glasgow coma scale (GCS) (β: 0.413, P-value <0.001) were the risk factors identified as predictors of hypothermia. Conclusion: A significant proportion of trauma patients were hypothermic on admission to the ED. Arrival CBT, length of stay in the ED, arrival ambient temperature, and GCS had a significant role in the development or exacerbation of hypothermia. The results of this study highlight the need for giving special attention to the early detection and management of accidental hypothermia among trauma patients in the ED.